Genetic Control of Wiring Specificity in the Fly Olfactory System. Issue 1 (1st January 2014) - Hong, Weizhe; Luo, Liqun
Abstract: Precise connections established between pre- and postsynaptic partners during development are essential for the proper function of the nervous system. The olfactory system detects a wide variety of odorants and processes the information in a precisely connected neural circuit. A common feature of the olfactory systems from insects to mammals is that the olfactory receptor neurons (ORNs) expressing the same odorant receptor make one-to-one connections with a single class of second-order olfactory projection neurons (PNs). This represents one of the most striking examples of targeting specificity in developmental neurobiology. Recent studies have uncovered central roles of transmembrane and secreted proteins in organizing this one-to-one connection specificity in the olfactory system. Here, we review recent advances in the understanding of how this wiring specificity is genetically controlled and focus on the mechanisms by which transmembrane and secreted proteins regulate different stages of the Drosophila olfactory circuit assembly in a coordinated manner. We also discuss how combinatorial coding, redundancy, and error-correcting ability could contribute to constructing a complex neural circuit in general.